Hunter x hunter. Volume 5 - Togashi, Yoshihiro (Shonen Jump manga., 2022)
Gon's new friend Killua may have run away from home, but that doesn't mean his family is willing to let him leave. Killua's parents sent his older brother Illumi to keep an eye on him during the Hunter Exam, and now Illumi has convinced Killua to return to the family business of assassination. Gon is convinced that Killua must have been brainwashed, and sets out with Leorio and Kurapika to make an intervention. But before the newly-licensed Hunters can try to talk some sense into Killua, they have to make it past the unstoppable guard beast that is trained to eat all visitors!